Potential for Eco-efficiency of Water Resources in The School Environment - Yustika, Ana; Wahjoe Handini (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Water is a natural resource that humans and other living things need. Along with population growth, water consumption in Indonesia has increased. That is inversely proportional to water availability, which is decreasing. To overcome these problems, the concept used in this study is eco-efficiency. Eco-efficiency is a concept that seeks to increase economic and environmental efficiency when carrying out activities. This study aims to analyze the opportunities for enhancing the eco-efficiency of water resources in the school environment, specifically at SMA N 1 in Ambarawa. This type of research is known as descriptive research. The SWOT analysis method is used for data analysis. SMA N 1 Ambarawa's average total water consumption is in the wasteful category, at 20,898 liters daily. The potential for implementing eco-efficiency in SMA N 1 Ambarawa regarding water consumption is high. The volume of water consumed in SMA N 1 Ambarawa is efficient, at 7,326 liters daily. However, there are significant leaks of technical and non-technical water, amounting to 13,572 liters. Several efforts can be implemented through no-cost, middle-cost, and high-cost recommendations to increase the eco-efficiency potential in water at SMA N 1 Ambarawa.